Gut Microbiota Combined With Metabolomics Reveals the Repeated Dose Oral Toxicity of β-Cyclodextrin in Mice - Lv, Shuangyu; Zhang, Xiaomei; Feng, Yu; Jiang, Qiying; Niu, Chenguang; Yang, Yanjie; Wang, Xinchun (Frontiers in Pharmacology, 2021)
Βeta-cyclodextrin (β-CD) with hydrophobic cavity enables formation of inclusion complexes with organic molecules. The formation of host–guest complexes makes application of β-CD popular in many fields, but their interaction with organisms is poorly understood. In the present study, the effect of β-CD on gut microbiota (16S rRNA gene sequencing), serum metabolites (gas chromatography–mass spectrometry platform) and their correlation (Pearson correlation analysis) was investigated after 14 days repeated oral exposure in mice. β-CD did not significantly affect the α-diversity indexes, including Richness, Chao1, Shannon and Simpson indexes, but disturbed the structure of the gut bacteria according to the result of principal component analysis (PCA). After taxonomic assignment, 1 in 27 phyla, 2 in 48 classes, 3 in 107 orders, 6 in 192 families, and 8 in 332 genera were significantly different between control and β-CD treated groups. The serum metabolites were significantly changed after β-CD treatment according to the result of unsupervised PCA and supervised partial least squares-discriminant analysis (PLS-DA). A total of 112 differential metabolites (89 downregulated and 23 upregulated) were identified based on the VIP >1 from orthogonal PLS-DA and p < 0.05 from Student’s t-test. The metabolic pathways, including ABC transporters, pyrimidine metabolism, purine metabolism, glucagon signaling pathway, insulin signaling pathway, and glycolysis/gluconeogenesis, were enriched by KEGG pathway analysis. Our study provides a general observation of gut microbiota, serum metabolites and their correlation after exposure to β-CD in mice, which will be helpful for future research and application of β-CD.